2018
DOI: 10.1007/s11695-018-3117-z
|View full text |Cite
|
Sign up to set email alerts
|

ABSI (A Body Shape Index) and ARI (Anthropometric Risk Indicator) in Bariatric Surgery. First Application on a Bariatric Cohort and Possible Clinical Use

Abstract: 2814.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Enhancing the BMI-based risk stratification with ABSI is potentially useful, as it would outline higher-risk subgroups for closer follow-up and monitoring for metabolic complications. Some combined applications of ABSI with BMI in clinical settings have already been described [45][46][47] . Although Krakauer & Krakauer have argued that joining ABSI, HI, BMI and height in a combined Anthropometric Risk Indicator (ARI) achieves better risk prediction compared to the individual components 47 , combining ABSI and BMI in a single index would prevent evaluating individually the risks arising from general and abdominal adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing the BMI-based risk stratification with ABSI is potentially useful, as it would outline higher-risk subgroups for closer follow-up and monitoring for metabolic complications. Some combined applications of ABSI with BMI in clinical settings have already been described [45][46][47] . Although Krakauer & Krakauer have argued that joining ABSI, HI, BMI and height in a combined Anthropometric Risk Indicator (ARI) achieves better risk prediction compared to the individual components 47 , combining ABSI and BMI in a single index would prevent evaluating individually the risks arising from general and abdominal adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we for the first time evaluated, for mortality prediction in the general population, the combination of a systematically selected set of independent anthropometrics (H, BMI, ABSI, and HI, whose respective attributable hazards were summed to give ARI) with MS. We found that although ARI was the best single mortality predictor and was positively correlated with all MS components, the clinical and laboratory data that contribute to the MS score could be used synergistically with ARI to further improve mortality prediction. Such individualized risk information could potentially be useful in a variety of clinical contexts for guiding personalized medical care [ 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that ABSI is independent of BMI, and more accurately than WC to be a substantial marker of arterial stiffness in Japanese adults 28. Among persons who received bariatric surgery in the USA, baseline ABSI could predict change in mortality risk at 3-year after surgery, but baseline BMI did not 40…”
Section: Discussionmentioning
confidence: 99%